REMOVAL OF AROMATICS AND SULFUR FROM LUBRICATING OIL BASE STOCK BY LIQUID EXTRACTION USING IONIC LIQUIDS - JASSIM AL KAISY, GHASSAN MAHMOUD (2015)
The interest in producing high class lubricating oil base stock (base oil) has received a considerable attention in the recent years. This was driven by the strict environmental regulations and higher product specifications to meet better performance required by the end users. Thebase oil of Group I class is conventionally produced through solvent treatment process, while a hydroprocessing are required for the production of higher class base oil of Group II & III which have lower aromatic (less than 10%) and sulfur content (less than 300 ppm) compared to GROUP I, according to American Petroleum Institute classification. However, the significant investment coupled with the severe operating conditions, i.e., high temperature and pressure, high hydrogen demand, expensive catalyst and high environmental impact have led to the necessity of developing better alternative involving milder operating conditions with lower investment cost and environmental impact.